2015
DOI: 10.1016/j.neurobiolaging.2014.01.154
|View full text |Cite
|
Sign up to set email alerts
|

Higher homocysteine associated with thinner cortical gray matter in 803 participants from the Alzheimer's Disease Neuroimaging Initiative

Abstract: A significant portion of our risk for dementia in old age is associated with lifestyle factors (diet, exercise, and cardiovascular health) that are modifiable, at least in principle. One such risk factor – high homocysteine levels in the blood – is known to increase risk for Alzheimer’s disease and vascular disorders. Here we set out to understand how homocysteine levels relate to 3D surface-based maps of cortical gray matter distribution (thickness, volume, surface area) computed from brain MRI in 803 elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 77 publications
0
38
0
1
Order By: Relevance
“…We recently reported that older adults with higher homocysteine levels had more pronounced regional brain atrophy (13) and thinner cortical gray matter (14) on MRI. We also found that the C677T variant in MTHFR was associated with smaller regional brain volumes in two independent elderly cohorts with mild cognitive impairment (MCI) (15).…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that older adults with higher homocysteine levels had more pronounced regional brain atrophy (13) and thinner cortical gray matter (14) on MRI. We also found that the C677T variant in MTHFR was associated with smaller regional brain volumes in two independent elderly cohorts with mild cognitive impairment (MCI) (15).…”
Section: Introductionmentioning
confidence: 99%
“…It is directly toxic to neurons and blood vessels and can induce DNA strand breakage, oxidative stress, and apoptosis [11]. The role of HCY as a potential and predictive biomarker in Alzheimer's disease [12], cognitive impairment [13], and autism [14] has been well recognized. Studies in other countries report the same dose-response relationship between homocysteine and vascular disease [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Brain neuroimaging revealed an association between elevated tHcy and lower subcortical brain volumes and cortical thickness, volume, and surface area in elderly people [60]. Vitamin B treatment has been shown to slow brain volume shrinkage [61], prevent atrophy of gray matter [62], and slow cognitive decline in people with mild cognitive impairment [63], an effect that was not confirmed by all studies [64].…”
Section: Folate Aging and Populationattributable Risk Of Diseasesmentioning
confidence: 99%